Peningkatan Hasil Belajar Bahasa Indonesia Melalui Metode Bermain Peran (Role Playing) Di Kelas V SD Negeri 224 Pallawa - Nasirah Nasirah (Publikasi Pendidikan, 2017)
The main problem in this research is how role play method can improve the students’ learning achievement Indonesian language course subject of fifth grade in SD Negeri 224 Pallawa Soppeng Regency. This study aims to find out how the application of role play in Indonesian language of the fifth grade students of SD Negeri 224 Pallawa Soppeng Regency.The approach used in this research is a qualitative and quantitative approach and this type of research is a classroom action research, consisting of two cycles where each cycle is held in two meetings. The research procedure includes planning, action, observation and reflection. The subjects in this study are26 students of the fifth grade of SD Negeri 224 Pallawa Soppeng Regency .The focus in this research is role play method and the students' learning outcomes. Data collection techniques used are observation and test. Data of learning achievement of Indonesian language were obtained by scoring and tabulating then calculating the average frequency value and the percentage.The results showed that there was an increase in student learning activity from cycle I in which those categorized as good turn to be very good category in cycle II. Based on the increase in learning outcomes in the second cycle as mentioned previously, it can be interpreted that the revision of actions taken in the second cycle in the learning process by role play method is proved effective. The student's ability has improved; the students’ problem in the first cycle in which they lack of elaborating learning messages through role play methods in the learning group has been resolved